2016
DOI: 10.1007/s10639-016-9507-8
|View full text |Cite
|
Sign up to set email alerts
|

Exploring relationships among TPACK constructs and ICT achievement among trainee teachers

Abstract: Teaching in the classroom today can no longer sustain the interest of students and be effective if the process involves traditional approach -teachers as sole provider of content information. In recent years technology has played a significant role in transforming education to more progressive and interactive activities. However the use of technology itself does not produce positive results in quality of learning and students' achievement. Teachers must be competent in subject knowledge, pedagogical skills and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 30 publications
2
41
0
5
Order By: Relevance
“…Also, correlational studies were implemented. For example, Khine, Ali and Afari (2017) found in their study that TK, PK, CK and TPK were significant predictors of TPK, TPACK and PCK, with the exception of CK which did not significantly relate to PCK and also PCK did not significantly relate to TPACK.…”
Section: Pedagogical Content Knowledge (Pck)mentioning
confidence: 90%
“…Also, correlational studies were implemented. For example, Khine, Ali and Afari (2017) found in their study that TK, PK, CK and TPK were significant predictors of TPK, TPACK and PCK, with the exception of CK which did not significantly relate to PCK and also PCK did not significantly relate to TPACK.…”
Section: Pedagogical Content Knowledge (Pck)mentioning
confidence: 90%
“…As suggested by Khine et al (2017), many studies have been carried out in different national contexts, but very few of them investigated the national and cultural context as a possible element influencing TPACK. For instance, Chang et al (2015) explored the TPACK perceptions of two physics instructors from China and Taiwan.…”
Section: Demographic Factors Influencing Individual Tpackmentioning
confidence: 99%
“…The fact that the pre-and post-study scores were significantly different in favor of the posttests suggests that it is important for teacher candidates to have the opportunity to make self-evaluations. It is needed to develop the teacher candidates'effective specific level of TPACK in their subject area (Khine et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Voogt et al (2013) in their literature review found that student-teachers do get experience in the design of technology-enhanced lessons but lack experiences in enacting technology based lessons. When we consider that technology integration is also an integral part of effective and efficient education, it is expected that teachers should improve their technological knowledge related to their current field content knowledge and their ability to use technology adequately in the teaching process (Gencosman, 2015;Khine et al, 2017).…”
Section: Technological Pedagogical and Content Knowledge (Tpck)mentioning
confidence: 99%